Respuesta :

Evaluate each expression individually and then combine like terms:

5 log₄(x²) = 5[tex]\frac{log (x^{2}) }{log (4) }[/tex] = 5[tex]\frac{log (x^{2}) }{log (2^{2}) }[/tex] = 5[tex]\frac{2 log (x) }{2 log (2) }[/tex] = 5 log₂x  = log₂x⁵

4 log₂(x) = log₂(x)⁴  =  log₂(x⁴)

**********************************************

   log₂(2x + 1) - 5 log₄(x²) + 4 log₂(x)

= log₂(2x + 1) - log₂x⁵ + log₂(x⁴)

= log₂[(2x + 1)*(x⁴) ÷ x⁵]

= log₂[tex]\frac{(2x+1)x^{4} }{x^{5}}[/tex]

= log₂[tex]\frac{2x+1 }{x}[/tex]